Poverty in Africa: pathways to viable escape strategies - Sunsuwa, Bala A. (Jos, Nigeria Balhan Publishers, 2020)
The aim of this book is to provide understanding of the phenomenon of poverty and the type of antipoverty policies that evolved. It deals with policy issues with regards to poverty reduction - from overall national development strategy to specific interventions against poverty. The focus is on Africa with particular attention to Nigeria.
Includes bibliography
osc 19/02/2024
Loans
Keywords: Poverty; Africa